Cartera de productos turísticos de aventura que promueva el desarrollo sostenible en la zona centro de Manabí - Aucapiña Delgado, Juan Andrés (2023)
The purpose of the research was to design a portfolio of adventure tourism products that would allow sustainable development in the central zone of Manabí; it was developed under a mixed approach, at a non-experimental exploratory level, with bibliographic, documentary and field work; integrated by four phases, starting with a diagnosis through a characterization sheet, a SWOT was applied, highlighting that the greatest strength of the zone is the diversity of tourism resources that allow the development of activities related to alternative tourism. In the second phase, 20 tourist attractions for adventure tourism were evaluated, highlighting 7 in Manta, 2 in Portoviejo, 9 in Santa Ana and 2 in Montecristi, Rocafuerte lacks the infrastructure to develop adventure tourism due to the seasonality of its attractions and resources. In the third phase, the profiles, factors and motivations of the tourism demand were analyzed and a survey was applied, determining that the main target public are national tourists from the different cities as Pedernales, Santo Domingo and Pichincha. Finally, a product portfolio was designed focused on adventure tourism in sun and beach, and mountain tourism. The SMMP brand (Santa Ana - Montecristi - Manta and Portoviejo) was created to offer exciting and memorable experiences in Santa Ana, Montecristi, Manta and Portoviejo, promoting sustainable development and quality of life.